Readily available but how accessible? : An analysis of the web accessibility of healthcare-related resources (Journal of Accessibility and Design for All, 2023)
With advances in technology, more health information is readily available to the public. Individuals with disabilities rely on online healthcare-related resources to access educational information and promote informed decision-making in their care. The Web Content Accessibility Guidelines (WCAG) were created to provide universal web practices which complement the needs of all individuals, such as those with low vision or screen readers users. However, many websites and the resources within them (e.g., PDFs) do not prioritise WCAG, leaving individuals with disabilities at a disadvantage in terms of their autonomy and health literacy. The objective of this study is to investigate and describe the common web accessibility errors present on international occupational therapy and pediatric websites and the resources within them. This mixed methods study evaluates compliance to WCAG success criteria using automatic web accessibility evaluation tools, specifically WAVE and AChecker, and manual checks to capture the human element. Descriptive statistics were used to examine the frequency of errors across several success criteria within the sample websites and PDFs. A subsequent thematic analysis was used to further examine how and why these errors violate the WCAG success criteria. Through automatic evaluation tools, many websites and resources did not comply with numerous WCAG 2.0 success criteria. Through manual checks of the web pages and resources within them, 5 themes were identified: inaccessible images, challenges accessing additional resources, poor structural formatting, lack of tagging in PDFs, and minimal colour contrast. The results of this study can inform web developers and contributors (e.g., Occupational Therapists) on how to successfully produce accessible websites and PDFs to provide equal access to health information. In conclusion, this study adds to the current understanding that many public-facing websites and the resources within them (e.g., PDFs) are not accessible, including healthcare-related websites meant to support informed decision-making among individuals with disabilities.